Nitric oxide mediated inhibition of antigen presentation from DCs to CD4+ T cells in cancer and measurement of STAT1 nitration. Issue 1 (December 2017) - Markowitz, Joseph; Wang, Jiang; Vangundy, Zach; You, Jia; Yildiz, Vedat; Yu, Lianbo; Foote, Isaac; Branson, Owen; Stiff, Andrew; Brooks, Taylor; Biesiadecki, Brandon; Olencki, Thomas; et al.
Abstract Myeloid derived suppressor cells (MDSC) produce nitric oxide (NO) and inhibit dendritic cell (DC) immune responses in cancer. DCs present cancer cell antigens to CD4+ T cells through Jak-STAT signal transduction. In this study, NO donors (SNAP and DETA-NONOate) inhibited DC antigen presentation. As expected, MDSC isolated from peripheral blood mononuclear cells (PBMC) from cancer patients produced high NO levels. We hypothesized that NO producing MDSC in tumor-bearing hosts would inhibit DC antigen presentation. Antigen presentation from DCs to CD4+ T cells (T cell receptor transgenic OT-II) was measured via a [3 H]-thymidine incorporation proliferation assay. MDSC from melanoma tumor models decreased the levels of proliferation more than pancreatic cancer derived MDSC. T cell proliferation was restored when MDSC were treated with inhibitors of inducible nitric oxide synthase (L-NAME and NCX-4016). A NO donor inhibited OT II T cell receptor recognition of OT II specific tetramers, thus serving as a direct measure of NO inhibition of antigen presentation. Our group has previously demonstrated that STAT1 nitration also mediates MDSC inhibitory effects on immune cells. Therefore, a novel liquid chromatography-tandem mass spectrometry assay demonstrated that nitration of the STAT1-Tyr701 occurs in PBMC derived from both pancreatic cancer and melanoma patients.